2004
DOI: 10.1002/ana.20283
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac and respiratory failure in limb‐girdle muscular dystrophy 2I

Abstract: Mutations in the gene encoding fukutin-related protein cause limb-girdle muscular dystrophy 2I. In this multicenter retrospective analysis of 38 patients, 55.3% had cardiac abnormalities, of which 24% had developed cardiac failure. Heterozygotes for the common C826A mutation developed cardiac involvement earlier than homozygotes. All patients initially improved while receiving standard therapy. Independent of cardiac status, forced vital capacity was below 75% in 44.4% of the patients. There was no absolute co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
76
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(91 citation statements)
references
References 15 publications
13
76
0
2
Order By: Relevance
“…In the present study, a higher prevalence of cardiac involvement was seen in males (38%) vs females (18%) with LGMD2I. Poppe et al 11 reported a similar finding, in which 83% of males and 42% of females with LGMD2I had certain or possible cardiac involvement. Of the 38 patients with LGMD2I, 15 had cardiac involvement based on ECHO findings of left ventricular regional wall motion abnormality and 6 had possible cardiac involvement based on abnormal P wave notching on ECG.…”
Section: Lgmd2isupporting
confidence: 87%
“…In the present study, a higher prevalence of cardiac involvement was seen in males (38%) vs females (18%) with LGMD2I. Poppe et al 11 reported a similar finding, in which 83% of males and 42% of females with LGMD2I had certain or possible cardiac involvement. Of the 38 patients with LGMD2I, 15 had cardiac involvement based on ECHO findings of left ventricular regional wall motion abnormality and 6 had possible cardiac involvement based on abnormal P wave notching on ECG.…”
Section: Lgmd2isupporting
confidence: 87%
“…11 Clinically significant, dilated cardiomyopathy develops in approximately half of the patients, and it is independent of the severity of the skeletal muscle weakness. 87,88 There is also an important respiratory involvement in patients with FKRP mutations, manifesting initially as a drop in forced vital capacity followed by nocturnal hypoventilation on the basis of diaphragmatic weakness. In contrast to Duchenne and Becker muscular dystrophy, it is important to note that the respiratory failure can occur while the patient is still ambulatory.…”
Section: Lgmd2 Associated With Secondary Reduction In Alpha Dystroglycanmentioning
confidence: 99%
“…Cardiac disease may be detected pre-clinically to allow early introduction of prophylactic treatment (i.e, "routine" management of cardiomyopathy is indicated and in some cases even cardiac transplantation may be necessary). 87,88 Respiratory impairment may manifest first as diaphragmatic weakness, so investigation of respiratory muscle strength while lying as well as sitting is mandatory. Night-time ventilatory assistance should be introduced in a timely manner.…”
Section: Lgmd2 Associated With Secondary Reduction In Alpha Dystroglycanmentioning
confidence: 99%
“…Cardiac involvement has been reported in 29% to 62% of patients with LGMD2I (69)(70)(71)(72)(73). LV wall motion changes and dilated cardiomyopathy may begin as early as the teenage years.…”
Section: Lgmd2imentioning
confidence: 99%
“…LV wall motion changes and dilated cardiomyopathy may begin as early as the teenage years. A significant percentage of patients may develop symptomatic heart failure over time, beginning at a mean age of 38 years (range 18 to 58 years) (70); this is not always associated with severe muscle weakness (67,70). LGMD2I patients are also at risk for respiratory impairment and may require nocturnal ventilation (69,70).…”
Section: Lgmd2imentioning
confidence: 99%